2017
DOI: 10.1039/c7ra06777a
|View full text |Cite
|
Sign up to set email alerts
|

Why is sodium-intercalated graphite unstable?

Abstract: Na-ion batteries offer an attractive low-cost alternative to Li-ion batteries. Although graphite is used as the negative electrode in conventional Li-ion batteries, attempts to use it in Na-ion batteries have been hampered by the inability of Na to form graphite intercalation compounds (GICs) under moderate conditions. It is generally considered that this is due to the size mismatch between Na and the graphite interlayer spacings, but here we show with detailed first-principles calculations of Li, Na, K, Rb, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
156
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 38 publications
2
156
0
5
Order By: Relevance
“…202 All stable alkali metals have been shown to be capable of forming GIC/nanotubide intercalants, 167,203 although graphite intercalation of sodium typically leads to low stoichiometries and high-stage GICs attributed variously to the small size of the metal cations preventing intergraphitic distances reaching energy minima, 204 the less reducing nature versus lithium, and the weakness of the subsequent ionic bond between the graphenide sheets and sodium cations. 205,206 Pure stage-1 sodium GICs can be synthesized from decomposition of the so-called "superdense" GIC 204 NaC 2 (formed at 40 kPa), and ternary stage-1 sodium GICs may be formed through use of a cointercalating solvent, 207 heavy group 1 metal, 208 or trace oxygen. 209 The group 2 alkali earth metals calcium, strontium, and barium readily intercalate graphite, 210 while magnesium is more challenging (analogously to sodium) but readily forms ternary intercalation compounds alongside a group 1 metal.…”
mentioning
confidence: 99%
“…202 All stable alkali metals have been shown to be capable of forming GIC/nanotubide intercalants, 167,203 although graphite intercalation of sodium typically leads to low stoichiometries and high-stage GICs attributed variously to the small size of the metal cations preventing intergraphitic distances reaching energy minima, 204 the less reducing nature versus lithium, and the weakness of the subsequent ionic bond between the graphenide sheets and sodium cations. 205,206 Pure stage-1 sodium GICs can be synthesized from decomposition of the so-called "superdense" GIC 204 NaC 2 (formed at 40 kPa), and ternary stage-1 sodium GICs may be formed through use of a cointercalating solvent, 207 heavy group 1 metal, 208 or trace oxygen. 209 The group 2 alkali earth metals calcium, strontium, and barium readily intercalate graphite, 210 while magnesium is more challenging (analogously to sodium) but readily forms ternary intercalation compounds alongside a group 1 metal.…”
mentioning
confidence: 99%
“…Although Li and Na have similar chemical properties, it is difficult for Na + to intercalate into the layered graphene structure of graphite, which is unlike Li + intercalation in graphite. This is possibly due to thermodynamic restrictions . As a result, graphite is reported to have a very low capacity of <20 mA h g −1 for Na storage with conventional electrolytes .…”
Section: Anodesmentioning
confidence: 96%
“…This is possibly due to thermodynamic restrictions. [98] As a result, graphite is reported to have a very low capacity of <20 mA h g −1 for Na storage with conventional electrolytes. [4] This limitation can be circumvented by using cointercalation phenomena in an etherbased electrolyte.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…Quantum mechanical calculations by Liu et al revealed that this results from competing energetic trends in ionization energy and ion-substrate coupling, causing unfavorable formation energy. [59] This also explains the reason for the lower voltages obtained in SIBs and magnesium-ion batteries as compared to the other alkali and alkaline earth metals. [59] This also explains the reason for the lower voltages obtained in SIBs and magnesium-ion batteries as compared to the other alkali and alkaline earth metals.…”
Section: Sodium-ion Batterymentioning
confidence: 98%
“…[58] These energetic changes modify the chemical bonding nature between the alkali metal and carbon, wherein weakening ionic bonding is observed from cesium to sodium due to the decrease in ionic size, culminating with lithiumcarbon bonds containing a covalent component and a negative formation energy. [59] This also explains the reason for the lower voltages obtained in SIBs and magnesium-ion batteries as compared to the other alkali and alkaline earth metals. [58] This www.advancedsciencenews.com inability of sodium to intercalate has often been attributed to the insufficient interlayer spacing for graphite, [60] as reversible intercalation of sodium in expanded RGO has been demonstrated.…”
Section: Sodium-ion Batterymentioning
confidence: 98%